Therapeutic effects of a combination of Chinese quince and Saururus chinensis extract on allergic airway inflammation in an ovalbumin-induced asthma mouse model - Lee, Hye Jin; Kim, Ki Cheon; Lee, Woo Jin; Nam, Hyo Jung; Ryu, Su Jin; Kim, Seon Hyeok; Kim, Won Jun; Yoon, Jae Won; Lee, Tae-Hee; Jeong, Pan-Young (Frontiers in Nutrition, 2025)
BackgroundAllergic asthma involves chronic inflammation, airway remodeling, and hyperresponsiveness. Inhaled corticosteroids combined with long-acting β2 agonists are effective; however, some patients experience side effects, highlighting the need for safer natural alternatives suitable for long-term use. Chinese quince (Q) and Saururus chinensis (SC) are used to treat various diseases, including asthma and inflammation. Q and SC extracts contain bioactive compounds that help modulate airway inflammation. Therefore, combining the two may enhance their immunomodulatory effects. However, the effects of a Q/SC mixture on allergic asthma remain unclear. The aim of this study is to assess the therapeutic effectiveness of a Q/SC mixture in treating asthma.MethodsThe therapeutic efficacy of the Q/SC extract was evaluated in an ovalbumin (OVA)-induced allergic airway inflammation model. After euthanasia, we assessed cell counts, cytokine expression in the bronchoalveolar lavage fluid (BALF), blood immunoglobulin (Ig) E levels, inflammatory cell infiltration, mucus production in the lung tissue, and the expression of protein and cytokine.ResultsA high-concentration Q/SC extract significantly reduced total cell and eosinophil counts, cytokine expression in BALF, and serum IgE levels. Furthermore, it reduced the expression of type 2 cytokines (IL-4, IL-5, IL-13) and inducible nitric oxide synthase in lung tissue. The extract also attenuated inflammatory cell infiltration and mucus production while inhibiting the STAT6 signaling pathway.ConclusionA high concentration of Q/SC extract effectively alleviates allergic airway inflammation by reducing eosinophilic inflammation, type 2 cytokine secretion, and mucus hyperproduction. This suggests that it could be a potential remedy for managing allergic airway inflammation.